Machine-made lace, the spaces of skilled practices and the paradoxes of contemporary craft production. (January 2018) - Fisher, Tom; Botticello, Julie
This article inspects a set of paradoxes that appeared in an investigation of contemporary industrial craft in the last remaining factory making machine lace in the United Kingdom. Its focus on a single site, set against a now global industry, means it can build on work in cultural and economic geography to understand this setting as a heterogeneous space, with links to a range of material and immaterial lineages, practices and networks. Ethnographic fieldwork on the factory floor at Cluny Lace threw up three paradoxes inherent in the firm's continued survival in a context of industrial decline. The first of these paradoxes is the re-concentration of material and immaterial resources in the factory both despite and as a result of the global restructuring of the textile industry. The second is the embodiment of knowledge, and therefore craft skill, both within persons and distributed through the worker's material environments. Third, is the recognition that the skilled practice the workers carry is not uniform but is multiple, resulting from an unequal distribution of opportunities within the lace industry and different versions of practice that result from the re-concentration of human capital in the factory. This article demonstrates that skill is not uncontested, but is power-ridden and value-laden, and transcends scale. It shows that knowledge and skill are not bound within an individual but are distributed among social actors, material objects and locales, where an attention to each is necessary for understanding the spaces of skilled practices and the ongoing survival of contemporary industrial craft production.